COLLEGE STUDENTS' CELL PHONE USE, BELIEFS, AND EFFECTS ON THEIR LEARNING. - ELDER, ANASTASIA D. (College Student Journal)
The purpose of this study is to explore college students' self-reported cell phone use and beliefs and investigate the effect on student learning. Eighty-eight college students responded to a questionnaire about their use of cell phones during classes, studying, and driving and about their beliefs about how cell phones impact their schoolwork. In addition, a subset (n= 34) participated in an experimental study in which half the students listened to a novel lecture without cell phones and half were told to use cell phones (e.g. play games, text) during the lecture. Descriptive results indicated that there is an acceptance of use in class; students' beliefs were neutral about whether they felt distracted or if time spent using devices affected their study time. Experimental results failed to indicate any difference in quiz scores between those using devices while listening to a lecture and those who did not. Yet, those who used their cell phones did anticipate lower scores than students who did not, indicating students may intuit its distracting nature for learning.